Making Chopper Machines to Improve the Quality and Quantity of Goat and KUB Chicken Business Feed - M. Faiz Firdausi; Danny Umar Siddiq; Novia Lailatul Fitri (TGO Journal of Community Development, 2026)
The purpose of this activity is to improve the efficiency of feed provision in the goat and chicken farming business of Kampung Unggul IAARD (KUB) through the manufacture and application of the Chopper machine. The activity was carried out in the Real Work Lecture (KKN) program in East Kasiyan Village, Puger District, Jember Regency. The implementation method consists of observation, design and design, implementation, and evaluation. The resulting Chopper machine has a production capacity of ±250 kg/hour with a smoother and uniform 1-2 cm shredding result. Trials showed that the time of chopping 8.5 kg of feed, which previously required ±30 minutes manually, was reduced to ±10 minutes with the Chopper machine. This result has an impact on increasing time and effort efficiency, better feed quality, and increased livestock productivity. In addition, training on the use and maintenance of machines also strengthens partners' independence in operating appropriate technology in a sustainable manner.